2015
DOI: 10.1103/physrevstper.11.010102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lecture instruction on student performance on qualitative questions

Abstract: The impact of lecture instruction on student conceptual understanding in physics has been the subject of research for several decades. Most studies have reported disappointingly small improvements in student performance on conceptual questions despite direct instruction on the relevant topics. These results have spurred a number of attempts to improve learning in physics courses through new curricula and instructional techniques. This paper contributes to the research base through a retrospective analysis of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
11
1
Order By: Relevance
“…We also found that prior physics experience, even in the immediate past, is not a significant factor [9]. This phenomenon is not unique to this context-it is well known in physics that certain incorrect reasoning patterns are observed both before and after formal instruction with roughly equal frequencies [13]. In contrast to Sattizahn et al, we view this as evidence that the underlying topic-specific intuitive ideas do not interact strongly with formal instruction.…”
Section: Discussioncontrasting
confidence: 57%
“…We also found that prior physics experience, even in the immediate past, is not a significant factor [9]. This phenomenon is not unique to this context-it is well known in physics that certain incorrect reasoning patterns are observed both before and after formal instruction with roughly equal frequencies [13]. In contrast to Sattizahn et al, we view this as evidence that the underlying topic-specific intuitive ideas do not interact strongly with formal instruction.…”
Section: Discussioncontrasting
confidence: 57%
“…The percentage of correct answers in this case was about 25%. Since the variation we typically see on pretests from quarter to quarter and from class to class is typically about ±5% [5], this result suggests that standard lecture instruction results in something like a 10% improvement on the task.…”
Section: Preliminary Investigationmentioning
confidence: 83%
“…This choice was pragmatic: many of the instructors who participated in our study were reluctant to ask students to respond to questions about energy before it was discussed in their courses. Other analyses suggest that the timing of conceptual questions does not affect student performance [141]; however, this may not be true for resources-oriented work, especially given our assumption that the context will affect which resources are activated. …”
Section: Discussionmentioning
confidence: 95%